Implementasi Manajemen Strategik dan Hubungannya Dengan Keberlangsungan (Going Concern) Usaha - Mutinda Teguh Widayanto; Dedi Joko Hermawan; Junaidi; Mohammad Natsir (Sketsa Bisnis, 2020)
This research analyze how far The Micro, Small and Medium Enterprises (MSME) implement Strategic Management in their business and to examine the relationship between Strategic Management Implementation and Business Going Concern. The population is the MSMEs in Probolinggo Regency, and the sample selection uses purposive sampling. The Hypothesis Testing is to see the relationship between Strategic Management Implementation and Going Concern using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results show that the level of Strategic Management Implementation is at a high level, while the results of statistical tests show that there is a significant positive effect between Strategic Management Implementation and Business Going Concern. Refers to this reseach, the effort to enhance the MSMEs understanding on Strategic management should be done in order they could maintain and surviving their business.